Etiudy Romana Polańskiego - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Roman Polanski’s Short Films Director/writer/actor Roman Polanski is one of the central figures in the history of Film School in Łódź. This study provides a detailed and comprehensive introduction to examine cinematic and artistic values of his early short films made between 1955 and 1961 in Poland and in France before his professional feature length debut “Knife in the Water” (1962). In his essential work Marek Hendrykowski looks at these nine shorts with in-depth analysis and adopts both historical and theoretical approach, making use of poetics terms, close reading method and socio-cultural interpretation. In its treatment of Polanski’s études this unique study discusses why these films are important in so many aspects and attracitve from many points of view and they have come to symbolise and represent modern cinema in Poland of the 1950s and early 1960s.